EKSISTENSI HAK ULAYAT PADA MASYARAKAT HUKUM ADAT RANTEPAO TORAJA UTARA - I Dewa Ayu Widyani; L. Elly AM Pandiangan (to-ra, 2019)
Abstract Customary rights are the right of the customary law community to control of their land.Customary rights are recognized throught the provisions of articles (3),(5) of the agrarian legal baseline,the regency is still alive and does not conflict with the law,this research was conducted in Rantepao sub-distrct,north Sulawesi,to determine what factors influence the existence of customary rights and how their legal protection from the government.This type of research is empirical juridical with primary and secondary data,so that the conclusion is obtained that the existence of customary land right in north Toraja Rantepao sub-distric is still recognized despite its weakening. Keyword : the existence of customary rights,customary rights of customary law communities, Rantepao North Sulawesi.